Determinants of farmers’ adoption of adaptation measures in carbon-intensive agricultural areas: A case study in An Giang province, Vietnam - Quang, N.M.; Thien, N.P.N.; Thu, N.H.; Thoa, H.T.N.; Tho, T.M.; Hieu, L.M.; Thinh, D.Q. (Informa UK Limited, 2023)
Globally, agriculture is both a victim and contributor to anthropogenic global warming. While farmers’ climate change perception generally increases, a low-carbon agricultural transition is not always an easy choice. There are numerous studies looking at the constraints hampering farmers’ adoption of adaptation strategies in climate-prone areas worldwide. The extent to which their assertion applies to farmers in carbon-intensive agricultural areas with less experience of climate change effects, however, is not clear and cannot be assumed given the shared social and cultural specificities of the farming population. This paper seeks to address this gap by scrutinizing critical determinants of farmers’ adaptation action in agriculturally rich An Giang province, where climate change impacts are generally less evident. Intense crop cultivation in the province involves the liberal use of fertilizers, crop-residue burning, frequent tilling, and other harmful farming practices that release carbon. Primary data were collected through household surveys (n = 133), field observation, and in-depth interviews (n = 24). A chi-square (χ2) test and a binary logistic regression model was used to analyze the factors influencing farmers’ adaptation decisions. The results indicated that farmers’ adaptation intent and decisions in the research area were significantly determined by market accessibility, uncertainty/instability of existing crops, and extreme weather conditions. These findings shed new light on approaches that are likely to motivate or hamper farmers’ climate-friendly transition in carbon-intensive agricultural hubs. We suggest that adaptive farming initiatives that have the potential to improve marketability and sustainability should be a starting point for mobilizing farmers for a low-carbon farming transition.